Analisis Pengaruh NPL, DER, dan CAR Terhadap ROA Pada PT Bank J Trust Indonesia Tbk. - Syahrin, Alfin; Alwi, Alwi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
This study aims to examine the effect of Non-Performing Loans (NPL), Debt to Equity (DER), and Capital Adequacy Ratio (CAR) on return on assets (ROA). This type of research includes associative research with a quantitative approach using secondary data obtained from the website www.idx.co.id. The population in this study is the financial statements of Pt Bank J Trust Indonesia Tbk for 15 years (2007-2021). The method used in selecting the sample was purposive sampling and determining the sample based on the criteria set by the researcher with a sample of 12 years (2010-2021). Based on secondary results of data processing using the F test method, it is known that the variables NPL, DER, and CAR simultaneously have a significant effect on ROA.